2015
DOI: 10.1186/s12889-015-1719-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of isoniazid preventive therapy on incidence of tuberculosis among HIV-infected clients under pre-ART care, Jimma, Ethiopia: a retrospective cohort study

Abstract: BackgroundTuberculosis (TB) is a major public health problem that accounts for almost half a million human immunodeficiency virus (HIV) associated deaths. Provision of isoniazid preventive therapy (IPT) is one of the public health interventions for the prevention of TB in HIV infected individuals. However, in Ethiopia, the coverage and implementation of IPT is limited. The objective of this study is to compare the incidence rate of TB, TB-free survival time and identify factors associated with development TB a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

21
49
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(76 citation statements)
references
References 26 publications
21
49
1
5
Order By: Relevance
“…Patients who had not taken IPT were more likely to develop TB as compared to those who took IPT. This finding is congruent with previous studies conducted in different parts of Ethiopia [17,18,22,36], which may reflect the role of IPT in reducing the occurrence of TB among PLHIV [16,38]. As a result, all HIV positive individuals who have no evidence of active TB infection should be taking IPT to prevent TB infection.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Patients who had not taken IPT were more likely to develop TB as compared to those who took IPT. This finding is congruent with previous studies conducted in different parts of Ethiopia [17,18,22,36], which may reflect the role of IPT in reducing the occurrence of TB among PLHIV [16,38]. As a result, all HIV positive individuals who have no evidence of active TB infection should be taking IPT to prevent TB infection.…”
Section: Discussionsupporting
confidence: 91%
“…For example, the Ministry of Health (MOH) decentralized TB/HIV co-infection care services from hospitals to health centers and strengthened referral systems to improve TB care and treatment at the community level [13]. In addition, early initiation of ART and early screening of TB, prior to provision of Isonized Preventive Therapy (IPT) [14,15] and Cotrimoxazole Prophylactic Therapy (CPT), were interventions implemented to reduce the incidence of TB among PLHIV [16][17][18][19][20].…”
mentioning
confidence: 99%
“…This might be due to the synergist role of IPT and ART drug in reducing the incidence of TB among PLHIV. Introduction of IPT to those patients on ART reduces the mycobacterium load which intern reduces the progression of latent TB to active one (32)(33)(34). This finding is consistent with those studies in Ethiopia (17, 28, 35, 36).…”
Section: Discussionsupporting
confidence: 90%
“…Similar studies in Sub-Saharan Africa that utilized routinely collected data observed similar temporal dynamics [55][56][57][58]. A possible explanation could be HIV drives TB related incidences, therefore, the incidence and prevalence of TB increases (decreases) with increasing (decreasing) HIV trends [59][60][61].…”
Section: Discussionsupporting
confidence: 55%